2021
DOI: 10.3390/plants10081555
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Reference Genes for Quantitative PCR in Johnsongrass (Sorghum halepense L.) under Glyphosate Stress

Abstract: Weeds are one of the main causes of the decrease in crop yields, with Johnsongrass (Sorghum halepense L.) being one of the most significant. Weeds can be controlled by herbicides, but some have developed resistance. Quantitative PCR is the technique of choice for studying gene expression related to herbicide resistance because of its high sensitivity and specificity, although its quantitative accuracy is highly dependent on the stability of the reference genes. Thus, in this study we evaluated the stability of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 43 publications
1
3
0
Order By: Relevance
“…For example, the level of expression for HSP70 exceeds that observed in heat-sensitive genotypes, indicating its superior protective effect against heat stress [60], However, its expression level may not be well reflected under other stress conditions. Furthermore, the expression of HSP70 was unstable under herbicide stress of Johnsongrass (Sorghum halepense) [7], and similar results were found in this study. Upon analyzing all samples, the expression of HSP70 was found to be the most unstable, and this pattern was consistent under both cold and drought stress.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…For example, the level of expression for HSP70 exceeds that observed in heat-sensitive genotypes, indicating its superior protective effect against heat stress [60], However, its expression level may not be well reflected under other stress conditions. Furthermore, the expression of HSP70 was unstable under herbicide stress of Johnsongrass (Sorghum halepense) [7], and similar results were found in this study. Upon analyzing all samples, the expression of HSP70 was found to be the most unstable, and this pattern was consistent under both cold and drought stress.…”
Section: Discussionsupporting
confidence: 89%
“…This technique plays a crucial role in investigating plant gene expression patterns under various conditions. Traditionally, certain housekeeping genes like ACT, TUB, UBC, etc., are commonly employed as reference genes [5][6][7]. However, it is important to note that the expression levels of these genes may vary under various experimental settings.…”
Section: Introductionmentioning
confidence: 99%
“…Palakolanu et al found that PP2A and CYP were the reference genes with the best performance under abiotic stress in sorghum [35]. María et al found that ARI 8 and PP2A were the top ranks under glyphosate stress in sorghum [36]. Otherwise, eIF4α and PP2A always express stably in Larix olgensis, Vaccinium corymbosum × angustifolium, Chenopodium quinoa Willd, oat, Suaeda glauca L., and so on, especially in salt stress and drought stress [37][38][39][40][41].…”
Section: Discussionmentioning
confidence: 99%
“…Selecting out the stable reference genes of plant species is very important in gene expression research on the biosynthetic pathway of their main components [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ]. In this study, based on the traditional housekeeping gene identity and the reports of plant stable internal reference genes in the literature [ 40 , 41 , 42 ], 15 candidate reference genes from D. huoshanense , namely GAPDH , eIF , EF-1α , PP2A , UBCE , RPL5 , TBP , APT1 , MDH , PTBP3 , PEPC , CYP71 , NCBP2 , TIP41 , and F-box , were assessed their expression stability by qPCR under abiotic stresses, namely oxidative (H 2 O 2 ), drought (PEG), cold (4 °C), UV radiation (UV), and hormone treatment (methyl jasmonate (MeJA)), as well as in different tissues (root, stem, and leaf). Next, geNorm [ 43 ], NormFinder [ 44 ], and BestKeeper [ 45 ] were preliminarily employed to analyze the gene expression stability, and RefFinder ( (accessed on 1 August 2021)) was then used to comprehensively reassess the candidate genes.…”
Section: Introductionmentioning
confidence: 99%